Gastrointestinal nematodes of equine in the region of Thessaloniki - THEODORIDIS (Ι. ΘΕΟΔΩΡΙΔΗΣ), Y.; FOUNTA (Α. ΦΟΥΝΤΑ), A.; GEORGOULAKIS (Ι. ΓΕΩΡΓΟΥΛΑΚΗΣ), I. (Journal of the Hellenic Veterinary Medical Society, 2018)
During a period of approximately two months (January-February 1995), 91 out of 119 riding horses of the seven riding clubs of Thessaloniki their feces were examined. The purpose of this survey was to find out and identify parasites after examining their reproductive elements. In the feces of the horses of two riding clubs had not been found any reproductive elements, while in the remaining five were found strongylid eggs in population whieh ranged from 2-5 to 85-94 / g of feces; per club ( rate infection 68; 1 %). After the examination of the 3rd stage larval, which obtained from fecal culture, were identified, from large strongylids (sub-family Strongylinae), the species Triontophorus sp (42%), Strongylus equinus (29%), Strongylus edentatus (21 %), Strongylus vulgaris (6%), and Trichostrongylus axei (2%) from the family of Trichostrongylidae. From the small strongylids (sub-family Cyathostominae) were identified the genera Cyathostomum (42%), Cylicostephanus (24%), Gyalocephalus (22%) and Poteriostomum (12%). The identified genera Triontophorus, Gyalocephalus and Poteriostomum as well as the species Trichostrongylus axei, are mentioned for the first time in horses in greek region.